Does VC Reputation Affect Function of Lockup Agreement? - HE, Kejia (Institutional Knowledge at Singapore Management University, 2009)
Instead of perceiving lockup agreement and VC-backing as exogenous variables, this paper employs the VC-backed IPO data and takes a closer examination on the specific effect of VC reputation, which impacts the choice of lockup length and return and volume abnormality around lockup expiry. Contrary to the commitment hypothesis proposed by previous literatures, the data suggests that less VC-backed companies tend to choose a longer lockup agreement as a compensation device and those companies backed by more reputable VC experience less negative abnormal return and less abnormal volume around lockup expiry.